Hazard Identification, Risk Assessment, and Determining Control (HIRADC) Analysis as an Occupational Health and Safety Risk Control Measure at Mychotech Lab - Choerudin Choerudin; Lazania Farah Alya; Milawati Milawati; Riny Yolandha Parapat (PT Ilmu Data Indonesia, 2026)
MYCL (Mycotech Lab) is a biomaterial company that develops sustainable leather alternatives using mushroom mycelium through a circular economy approach. One of its main products, Mylea, is a mycelium-based leather material developed for fashion and lifestyle applications. Although this production process provides environmental benefits compared with conventional leather and synthetic materials, it still involves occupational safety and health (OSH) risks. Workers may be exposed to biological hazards, chemical agents, high-temperature equipment, mechanical hazards, and ergonomic risks during production activities. This study aims to identify workplace hazards, assess risk levels, and determine appropriate control measures in the mycelium leather production process at MYCL. The research applied a qualitative approach through direct observation, interviews, and documentation of production activities, including growth medium preparation, sterilization, inoculation, incubation, harvesting, pressing, drying, and finishing. Hazard identification and risk assessment were conducted using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. The results showed that identified hazards ranged from medium to very high risk levels. The highest risks were found in the sterilization process due to exposure to high-temperature autoclave surfaces and pressurized steam, as well as in the pressing and forming process involving hydraulic equipment. Other risks included contamination, biological exposure, ergonomic issues, and heat exposure. Recommended control measures include improving personal protective equipment (PPE) compliance, strengthening safety procedures, conducting routine equipment maintenance, improving workplace sanitation, implementing ergonomic practices, and providing worker training. The findings provide an overview of occupational risks in mycelium-based manufacturing and support safer and more sustainable industrial operations.